1988
DOI: 10.1210/endo-122-1-270
|View full text |Cite
|
Sign up to set email alerts
|

Localization of 7B2, Neuromedin B, and Neuromedin U in Specific Cell Types of Rat, Mouse, and Human Pituitary, in Rat Hypothalamus, and in 30 Human Pituitary and Extrapituitary Tumors

Abstract: The distributions of three novel peptides, 7B2, neuromedin B, and neuromedin U, in rat, mouse, and human pituitaries, rat hypothalamus, and 30 human pituitary tumors were investigated with immunocytochemistry. Immunoreactivity for 7B2 was present in rat, mouse, and human gonadotropes, in intermediate lobe cells and posterior lobe nerve fibers in rats and mice, in rat hypothalamus (particularly in the median eminence), and in eight human pituitary gonadotropinomas. In gonadectomized rats, larger, more numerous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
2
5

Year Published

1989
1989
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 0 publications
7
79
2
5
Order By: Relevance
“…Considering these results together, the reported action of neuromedin U on uterine tissue would appear to be primarily mediated by TGR-1. It has been reported that both neuromedin U mRNA and neuromedin U-like immunoreactivity are abundantly detected in the human and rat pituitary gland (17,24,25). We detected the highest level of neuromedin U mRNA expression in the rat pituitary gland (10).…”
Section: Discussionsupporting
confidence: 46%
“…Considering these results together, the reported action of neuromedin U on uterine tissue would appear to be primarily mediated by TGR-1. It has been reported that both neuromedin U mRNA and neuromedin U-like immunoreactivity are abundantly detected in the human and rat pituitary gland (17,24,25). We detected the highest level of neuromedin U mRNA expression in the rat pituitary gland (10).…”
Section: Discussionsupporting
confidence: 46%
“…Estudos imunocitoquími-cos revelaram co-localização de neuromedina B e TSH em adeno-hipófises de ratos, sugerindo que ela seja sintetizada pelos tireotrofos murinos (32,37).…”
Section: Neuromedina B E Grp Na Hipófiseunclassified
“…Houben et al (24) observaram aumento nos níveis de RNA mensageiro para neuromedina B após tratamento de cultura de células re-agregadas de hipófise com estrogênio. O conteúdo de neuromedina B na adeno-hipófise muda de acordo com a função tireóidea, estando aumentado no hipertireoidismo e diminuído em animais tireoidectomizados (37,38), indicando regulação de sua síntese pelos hormônios tireóideos (38).…”
Section: Neuromedina B E Grp Na Hipófiseunclassified
See 1 more Smart Citation
“…NPY, cholecystokinin, galanin, leptin, orexins, beacon and NPW) (11)(12)(13)(14)(15)(16)(17), also NMU appears to regulate the hypothalamic-pituitary-adrenal (HPA) axis. The expression of NMU and NMUR 2 was found in the hypothalamus and anterior pituitary (10,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), while in the adrenal glands only the expression of NMUR1 was detected (9,(27)(28)(29)33,34). NMU has been shown to enhance c-fos expression in the hypothalamic paraventricular nucleus (1,2,30,35), to increase CRH and vasopressin output from rat hypothalamic explants, and to stimulate ACTH and corticosterone secretion in the rat (2,4,5,(36)(37)(38).…”
Section: Introductionmentioning
confidence: 95%